UPAYA MENINGKATKAN KOMITMEN ORGANISASI MELALUI PERILAKU KEPEMIMPINAN - Ananda, Susi; Winata, Hendri (Universitas Pendidikan Indonesia, 2017)
This article aims to discuss the results of his research on the influence behavior against the commitment of the leadership of the organization in one of educational institutions in the city of bandung. A method of this research using methods explanasi survey, as the proportion of respondents as many as 57 people employees. The result analysis of the data indicate that the percentage the effectiveness of our leadership behavior was a little, and the percentage level employees komiten organization is also small. Nevertheless, behavior having influence leadership a positive and significantly to the commitment of the organization. To increase the commitment of the organization, then needs to be improved the effectiveness of our behavior leadership.ABSTRAKArtikel ini bertujuan untuk memaparkan hasil penelitian tentang pengaruh perilaku kepemimpinan terhadap komitmen organisasi di salah satu Institusi Pendidikan di Kota Bandung. Metode penelitian ini menggunakan metode survey explanasi, dengan responden sebanyak 57 orang pegawai. Hasil analisa data menunjukkan bahwa presentase efektifitas perilaku kepemimpinan masih rendah, dan presentase tingkat komiten organisasi pegawai juga rendah. Namun demikian, perilaku kepemimpinan memiliki pengaruh yang positif dan signifikan terhadap komitmen organisasi. Untuk meningkatkan komitmen organisasi, maka perlu ditingkatkan efektifitas perilaku kepemimpinan.